1996
DOI: 10.1177/01461672962212005
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Rusbult Model of Relationship Commitment and Stability in a 15-Year Study of Heterosexual Couples

Abstract: This study tested Rusbult's investment model of relationship commitment and stability using data from both partners of 167 heterosexual couples studied from 1972 to 1987. Multiple regression analyses generally confirmed predictions that rewards and costs account for a significant proportion of the variance in satisfaction and that satisfaction, investments, and quality of alternatives together account for a significant proportion of the variance in commitment. Evidence about the hypothesized mediational role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
107
4
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(120 citation statements)
references
References 18 publications
8
107
4
1
Order By: Relevance
“…However, in an independent test of the investment model, Bui, Peplau, and Hill (1996) noted that ''less clear support was found for the mediational components of Rusbult's model'' (p. 1256). Further, Rusbult, Verette, Whitney, Slovik, and Lipkus (1991) reported that the mediational effects of commitment were not evidenced when examining accommodation processes between romantic partners and commitment only partially mediated the relationships between the distal predictors of commitment and both cognitive interdependence , Study 1) and taking a partner's perspective (Arriaga & Rusbult, 1998, Studies 3 and 4).…”
Section: Implications For the Investment Modelmentioning
confidence: 98%
“…However, in an independent test of the investment model, Bui, Peplau, and Hill (1996) noted that ''less clear support was found for the mediational components of Rusbult's model'' (p. 1256). Further, Rusbult, Verette, Whitney, Slovik, and Lipkus (1991) reported that the mediational effects of commitment were not evidenced when examining accommodation processes between romantic partners and commitment only partially mediated the relationships between the distal predictors of commitment and both cognitive interdependence , Study 1) and taking a partner's perspective (Arriaga & Rusbult, 1998, Studies 3 and 4).…”
Section: Implications For the Investment Modelmentioning
confidence: 98%
“…Factors such as current relationship status and satisfaction, availability of potential romantic or sexual partners, and the mate value of romantic rivals all play a role in determining the expected payoff associated with attempts to enhance one's desirability (satisfaction, Bui, Peplau, & Hill, 1996;alternative mates, Kenrick, Neuberg, Zierk, & Krones, 1994;rivals, Gutierres, Kenrick, & Partch, 1999). Although these and similar situational effects operate outside the purview of what is typically conceptualized as the self, they may also be able to influence self-esteem.…”
Section: Two Studies Measured Self-esteem Across the Menstrual Cycle mentioning
confidence: 99%
“…Given that commitment represents more than simple positive evaluation-given that commitment encompasses the effects of such variables as investment size and normative support (Bui et al, 1996;Felmiee et al, 1990)---it seems unlikely that interactions with commitment are accounted for solely by the ability to bring to mind positive features of one's own relationship. Also, the commitment-superiority association was evident beyond variance attributable to ratings of specific relationship attributes.…”
Section: Alternative Interpretationsmentioning
confidence: 99%